Democracy beyond Athens : popular government in Greek classical a ge - Robinson, Eric W. (Cambridge, UK ; New York : Cambridge University Press, 2011)
"What was ancient democracy like? Why did it spread in ancient Greec e? An astonishing number of volumes have been devoted to the well-attes ted Athenian case, while non-Athenian democracy - for which evidence is harder to come by - has received only fleeting attention. Nevertheless , there exists a scattered body of ancient material regarding democracy beyond Athens, from ancient literary authors and epigraphic documents to archaeological evidence, out of which one can build an understanding of the phenomenon. This book presents a detailed study of ancient Gree k democracy in the Classical period (480-323 bc), focusing on examples outside Athens. It has three main goals: to identify where and when dem ocratic governments established themselves in ancient Greek city-states ; to explain why democracy spread to many parts of Greece in this perio d; and to further our understanding of the nature of ancient democracy by studying its practices beyond Athens"--
Introduction -- 1. Classical demokratiai on the Greek mainland (cent ral Greece and the Peloponnese) -- 2. Classical demokratiai in Western and Northwestern Greece (plus Cyrene) -- 3. Classical demokratiai in Ea stern Greece -- 4. The spread of democracy in the Classical period -- 5 . The nature of Classical democracy outside Athens.
Includes bibliographical references (p. 251-268) and index.
Keywords: Democracy -- Greece -- History -- To 1500.; Greece -- Politics and government -- To 146 B.C.